2020
DOI: 10.1177/1018529120977259
|View full text |Cite
|
Sign up to set email alerts
|

Agro-information Service and Information-seeking Behaviour of Small-scale Farmers in Rural Bangladesh

Abstract: Agriculture is the mainstay of Bangladesh’s economy, accounting for 15.89% of its GDP and 45.1% of its labour employment. Efficiency of economic activities in agriculture crucially depends on the flow of information relating to farming decisions, as well as on demand for such information by farmers. This study examines the information needs and information-seeking behaviour of small-scale farmers in rural Bangladesh. Opinions and feedback of farmers were collected through mini–focus group discussions (MFGD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…All the modes besides newspapers are still working very effectively and they benefitted with increased income and increased marketing opportunities by accessing marketing information from these modes of communication. Similar findings were observed by Rahman et al, (2016) & Rahman et al, (2020 studied the source of information for farmers of different areas of agricultural practices. Likewise, it was observed that in mountain regions, radio and television are the major source for communicating with farmers on how to protect and stimulate agricultural development.…”
Section: Resultssupporting
confidence: 87%
“…All the modes besides newspapers are still working very effectively and they benefitted with increased income and increased marketing opportunities by accessing marketing information from these modes of communication. Similar findings were observed by Rahman et al, (2016) & Rahman et al, (2020 studied the source of information for farmers of different areas of agricultural practices. Likewise, it was observed that in mountain regions, radio and television are the major source for communicating with farmers on how to protect and stimulate agricultural development.…”
Section: Resultssupporting
confidence: 87%
“…In addition to that, they have a moderate level of education and poor awareness regarding using of ICT equipment for the accessibility of agricultural information (Ranachandra, 2020). A similar findings has reported by Rahman et al, 2020 andChikaire et al,2015 in their research studies regarding the subsistence farming practices of women farmers and they do not use ICTs to the accessibility of agricultural information due to lower level of awareness about ICT usage of women farmers. Thus, there is a requirement of a considerable level of agricultural information about modern farming technologies .…”
Section: Agricultural Information Needs Of Women Farmers In the Areasupporting
confidence: 84%
“…However, poor access to the market, high market commission and inadequate market information were reported as the least severe constraints faced by the marketers. This may perhaps be attributable to the ease of communication and information sharing made possible by the use of mobile phones [39,40] and availability of extension agents [41] in the area.…”
Section: Constraints To Plantain Marketingmentioning
confidence: 99%